STUDI PEMODELAN SISTEM PENGONTROLAN SUHU RUANGAN BERBASIS LOGIKA FUZZY SUGENO - Sitti Amalia; Rafika Andari; Rudhi Syukriansyah; Sitti Amalia (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2020)
Fuzzy logic is part of an artificial intelligence system (Artificial Intelligence) that emulates the human ability to think in the form of an algorithm which is then run by a machine. Fuzzy logic can also be applied to control room temperature, so that the temperature becomes stable. One of the fuzzy logic controller models that is applied in solving the problem is Fuzzy Sugeno. Making this prototype aims to collect Sugeno fuzzy logic data with this tool so that the temperature in a room becomes stable as desired, this prototype work system is based on the temperature and humidity values read by the sensor then the fan will rotate according to the temperature and humidity. This research uses Sugeno fuzzy logic with temperature and humidity input and the output is fan rotation. The series of modeling system for room temperature control based on Sugeno fuzzy logic, which is designed to be able to regulate room temperature conditions for each temperature and humidity condition read by the sensor. Experimental results for the comparison between manual calculation and Matlab achieved 100% success. While the experimental results for the comparison between matlab and prototype have an average error of 36% from five experiments.